The Role of Psychology Towards Sustainable Development Goal 3: Good Health and Wellbeing in South Africa - Ntombophelo Sithole-Tetani (E-Journal of Humanities, Arts and Social Sciences)
The 2030 Agenda for Sustainable Development, as it is known, is a call to action to end poverty, protect the planet, and ensure prosperity for all. The third SDG, ‘Good Health and Wellbeing,’ aims to ensure healthy lives, promote well-being for all ages, and halt and reverse global illnesses such as HIV, tuberculosis, and the COVID-19 pandemic, etc. This paper used a narrative literature review to discuss the role of psychology in SDG3 in the South African Context. A narrative literature review is an extensive joining and assimilation of existing research on a specific issue, providing an overview of major discoveries and their interconnectedness. Findings revealed that despite the significant contributions that can be made by psychology, the barriers to integrating psychology into health systems are as complex as applying a psychological approach to achieving sustainable health outcomes. Barriers are recognized, and their resolution is facilitated within the context of social justice and human rights; the significant roles played by psychology can be enhanced, and the links to vision and TC can be better enabled. Furthermore, In South Africa, the barriers to the seamless integration of psychology into health systems are attributed to a lack of infrastructure, limited resources, and available services, human resources (clinical psychologists), effective training, and existing policies, which need to be addressed by the South African government.